Efficient and selective copper-grafted nanoporous silica in aqueous conversion of aldehydes to amides. Issue 1 (25th September 2014) - Rostamnia, Sadegh; Nouruzi, Nasrin; Xin, Hongchuan; Luque, Rafael
Abstract : The one-pot conversion of aldehydes to their corresponding primary amides has been studied using SBA-15-grafted ethylenediamine copper complexes (En–Cu). Abstract : The one-pot conversion of aldehydes to their corresponding primary amides has been studied using SBA-15-grafted ethylenediamine copper complexes (En–Cu). The heterogeneous catalyst could be readily isolated from the reaction mixture and reused at least 14 times without significant loss in activity. The influence of reaction parameters was studied and the conditions determining yields and selectivities, including quantity of catalyst, solvent and base, were optimized to afford amides in high yields. The structures of synthesized catalysts were investigated using different characterization techniques including Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), CHN, atomic absorption (AA), scanning electron microscopy (SEM) and transmission electron microscopy (TEM).